"Community conflict, partition and nationalism/ edited by Colin H. Williams and Eleonore Kofman" - "Kofman, Eleonore, (ed.)" (Londan : Routhledge, 1989)
This book attempts to explain the dynamics of community conflict, explores the relationship between cultural differences and political behaviour and examines the role of the state. It analyses the problems in many different societies. This book should be of interest to lecturers and introductory and intermediate students in human geography, political science, international studies and sociology.
Keywords: Violence